"Opening the Heart": An Interview with Steve Parker. (3rd April 2017) - Henderson, Robert
Abstract : In this interview, Dr. Parker talks about how important Jungian psychology has been to him, especially following his heart attack, and how he has worked with his dreams and symbolism to guide his recovery. His work has led him to build a stone labyrinth at his wilderness home outside Fairbanks, Alaska. Artwork and photographic images illustrates his healing adventure. A brief video can be viewed at:http://jungcurrents.com/stone-sanctuary .